An efficient heterodinuclear Ir(iii)/Pt(ii) complex: synthesis, photophysics and application in light-emitting electrochemical cells. Issue 34 (21st August 2019) - Shafikov, Marsel Z.; Tang, Shi; Larsen, Christian; Bodensteiner, Michael; Kozhevnikov, Valery N.; Edman, Ludvig
Abstract : A novel heterodinuclear Ir(iii )/Pt(ii ) complex delivers vibrant red phosphorescence with high efficiency in a light-emitting electrochemical cell. Abstract : We report on the design, synthesis, characterization and successful application of a heterodinuclear Ir(iii )/Pt(ii ) complex endowed with two 4, 6-diphenylpyrimidine ligands and two acetylacetonate ligands, with one of the former being the rigid bridging unit between the two metal centers. The heterodinuclear complex exhibits red phosphorescence with a high quantum yield of Φ PL = 85% and a short room-temperature decay time of τ = 640 ns in degassed toluene solution. The high efficiency of the spin-forbidden T1 → S0 transition is demonstrated to originate in a strong spin–orbit coupling of the T1 state with a manifold of excited singlet states, which contributes to the record-breaking zero-field splitting of the T1 state of 240 cm −1 . The high-solubility and non-ionic hetero-dinuclear complex was employed as the emissive guest compound in host–guest light-emitting electrochemical cells, and such optimized devices delivered vibrant red emission ( λ peak = 615 nm) with a second-fast turn-on and a high external quantum efficiency of 2.7% at a luminance of 265 cd m −2 .